A review on municipal solid waste-to-energy trends in the USA. (March 2020) - Mukherjee, C.; Denney, J.; Mbonimpa, E.G.; Slagley, J.; Bhowmik, R.
Abstract: This review on current US municipal solid waste-to-energy trends highlighted regional contrasts on technology adoption, unique challenges of each technology, commonly used decision support tools, and major operators. In US only 13% of MSW is used for energy recovery and 53% is landfilled. There are 86 WTE facilities that mostly use Mass-Burn and Refuse-Derived Fuel technologies and are concentrated in densely populated northeast (predominantly in New York) and the State of Florida. For the rest of the country most of the MSW ends up in landfills equipped with gas recovery, which is supplied to homes or used for electricity generation. However, there are many pilot and experimental systems based on advanced gasification and pyrolysis processes, which are viewed as potential technologies to respond to an issue of landfills nearing full capacity in various US states. These systems are viewed as "cleaner" (65% less toxic residue) than established mass burn technologies but not matured to commercialization due technical and cost hurdles. Operation and maintenance costs between $40-$100 per ton of MSW were reported for gasification systems. The heterogeneous nature of MSW, gas cleaning and air pollution controls are the main disadvantages. Key design and decision support tools used by the scientific community and major operators in US include: Techno-economic analysis, Life cycle sustainability assessment, and Reverse logistics modeling. A conclusion drawn from reviewed studies is that adoption of thermal WTE technologies in US could continue to increase, albeit slowly, in coastal and urban areas lacking suitable lands for new landfills. Graphical abstract: Image 1 Highlights: Existing Mass-Burn Incinerators of the US face public opposition due air emissions. Landfills with gas recovery remain dominant technology in Mid-West and West US. US Energy companies are experimenting with Gasification and Pyrolysis of waste. Plasma-arc gasification claim to reduce harmful pollutants but has challenges. Techno-economic, Life cycle analysis & Reverse-Logistics modeling gauge challenges.